Discovery of a Novel Multitarget Analgesic Through an In Vivo-Guided Approach - Guo Zhen; Nayeon Do; Nguyen Van Manh; Hee-Jin Ha; Hee Kim; Hyunsoo Kim; Kwanghyun Choi; Jihyae Ann; Jeewoo Lee (Pharmaceuticals)
Background: Pain is a complex condition influenced by peripheral, central, immune, and psychological factors. Multitarget approaches offer a more effective and safer alternative to single-target analgesics by enhancing efficacy, reducing side effects, and minimizing tolerance. This study aimed to identify a novel multitarget analgesic with improved pharmacological properties. Methods: An in vivo-guided screening approach was used to discover a new analgesic compound. Compound 29, derived from a novel scaffold inspired by opiranserin and vilazodone pharmacophores, was identified through analog screening in the formalin test. Its efficacy was further evaluated in the spinal nerve ligation (SNL) model of neuropathic pain. Mechanistic studies explored its interaction with neurotransmitter transporters and receptors, while pharmacokinetic and safety assessments were conducted to determine its stability, brain penetration, and potential toxicity. Results: Compound 29 demonstrated high potency in the formalin test, with an ED50 of 0.78 mg/kg in the second phase and a concentration-dependent effect in the first phase. In the SNL model, it produced dose-dependent analgesic effects, increasing withdrawal thresholds by 24% and 45% maximum possible effect (MPE) at 50 and 100 mg/kg, respectively. Mechanistic studies revealed strong triple uptake inhibition, particularly at dopamine (DAT) and serotonin (SERT) transporters, alongside high-affinity 5-HT2A receptor antagonism. Pharmacokinetic analysis indicated enhanced stability and blood–brain barrier permeability. In vitro studies confirmed its nontoxicity to HT-22 cells but revealed potential hERG inhibition and strong CYP3A4 inhibition. Conclusions: Compound 29 is a promising multitarget analgesic with potent efficacy and favorable pharmacokinetics. Ongoing optimization efforts aim to mitigate side effects and enhance its therapeutic profile for clinical application.